WHO Child Growth Standards in context: The Baby-bod Project - Observational study in Tasmania - Andrew P Hills; Nuala M Byrne; Kiran D K Ahuja; Sisitha Jayasinghe; Manoja P Herath; Jeffrey M Beckett (BMJ Publishing Group, 2021)
Objective This research evaluated (1) differences in body size and composition of Tasmanian infants at birth and 3 and 6 months postpartum compared with WHO child growth standards and (2) body composition changes in Tasmanian infants at the extremes of the weight-for-length (WFL) spectrum.Design Observational study.Setting A hospital in Northern Tasmania, Australia.Patients 315 healthy infants (~90% Caucasian) born between 2017 and 2019 in Tasmania.Interventions Body composition and anthropometric measures at 0, 3 and 6 months.Main outcome measures Growth characteristics at birth and growth trajectories from 0 to 6 months were compared against WHO child growth standards for 0-2 years.Results Overall, growth of Tasmanian infants in the first 6 months of life was similar to the global prescriptive standards. Trajectories of fat mass (FM) and fat-free mass (FFM) accrual in infants from the extremes of the size spectrum appear to converge at the 6-month time point. Infants in the lower extremity demonstrated the most precipitous accrual in percentage FM (and the steepest decline in percentage FFM), compared with all other infants.Conclusion No significant deviations of growth were observed in Tasmanian infants from 0 to 6 months in comparison to the WHO prescriptive growth standards. Infants below the third percentile WFL showed the most precipitous increase in FM accretion. Periodic comparisons local infants with global standards will enable identification of significant deviations from optimal growth patterns.